ANALISIS PROBLEMATIKA PEMBELAJARAN BAHASA ARAB BERDASARKAN ASPEK LINGUISTIK DAN NON-LINGUISTIK PADA PENDIDIKAN DASAR - Anisa Syahidatullah (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
This research is motivated by psychopedagogical gaps in elementary school students who appear active behaviorally in class but have low psychological interest in learning Arabic. The focus of the problem is directed at identifying the problems of Arabic learning in grade IV A students of MIN 6 Sukoharjo in the 2025/2026 academic year reviewed from linguistic and non-linguistic aspects. Using a qualitative approach with descriptive methods, the important stages of this research were carried out through natural classroom observations, structured interviews with teachers and students, and the collection of documentation of grades. Data were analyzed interactively including condensation, data presentation, and drawing conclusions. The research findings revealed that obstacles stem from three pillars of the educational ecosystem. From the student perspective, linguistic obstacles include low visual reading skills (maharah qira'ah), writing layout (kitabah), and vocabulary mastery (mufrodat), while non-linguistic factors are triggered by a crisis of self-confidence and intrinsic motivation. From the teacher perspective, obstacles include inconsistencies in academic backgrounds and class capacity loads that exceed ideal standards. In terms of material, there is a disparity between the difficulty level of textbooks and students' basic competencies. The main conclusion emphasizes that improving instructional quality must focus on gradual reconstruction of teaching materials and strengthening language symbols from an early age. ABSTRAK Penelitian ini dilatarbelakangi oleh kesenjangan psikopedagogis pada siswa tingkat dasar yang tampil aktif secara perilaku di kelas namun memiliki minat psikologis yang rendah terhadap pembelajaran Bahasa Arab. Fokus masalah diarahkan untuk mengidentifikasi problematika pembelajaran Bahasa Arab pada siswa kelas IV A MIN 6 Sukoharjo Tahun Ajaran 2025/2026 ditinjau dari aspek linguistik dan non-linguistik. Melalui pendekatan kualitatif dengan metode deskriptif, tahapan penting penelitian ini dilakukan melalui observasi kelas secara natural, wawancara terstruktur bersama guru serta siswa, dan pengumpulan dokumentasi nilai. Data dianalisis secara interaktif meliputi kondensasi, penyajian data, hingga penarikan kesimpulan. Temuan penelitian mengungkap bahwa kendala bersumber dari tiga pilar ekosistem pendidikan. Dari sisi siswa, hambatan linguistik mencakup rendahnya kemahiran membaca visual (maharah qira'ah), penulisan tata letak huruf (kitabah), dan penguasaan kosakata (mufrodat), sementara faktor non-linguistik dipicu oleh krisis kepercayaan diri dan motivasi intrinsik. Dari sisi guru, kendala berupa ketidaksesuaian latar belakang keilmuan serta beban kapasitas kelas yang melebihi standar ideal. Dari sisi materi, terdapat ketimpangan antara bobot kesulitan buku ajar dengan kompetensi dasar peserta didik. Simpulan utama menegaskan bahwa perbaikan mutu instruksional wajib berfokus pada rekonstruksi materi ajar secara bertahap dan penguatan simbol bahasa sejak dini.